Quantitative Methods for Accounting and Business Studies / Third Edition - Bancroft Gordon; O'Sullivan George (Mcgraw Hill Book Company, 1993)
This book incorporates new key management science topics, including chapters on linear programming, network analysis, stock control and simulation. Preface, Acknowledgements, Introduction, Graphs and Equations, Financial Arithmetic, Matrices, Elementary Calculus, Data Collection and Sampling, Describing Statistical Data, Summary Statistics, Regression and Correlation, Time Series, Index Numbers, Probability, Decision Analysis, Probability Distributions, Estimation, Hypothesis Testing, Chi-squared Tests, Additional Applications of Sampling, Linear Programming, Network Analysis, Stock Control, Simulation, Appendices, Solutions to Exercises, Statistical Tables, List of Formulae, Bibliography, Index.